Use of didactic potential of innovative tutorials in complete pedagogical process of the STEM-education centers - Lozitsky, Vyacheslav L. (Journal of the Belarusian State University. Journalism, 2019)
Subject of author’s consideration is the perspective of use of didactic potential of hi-tech tutorials in the centers of STEM-education as compound component of the innovative approach based on application in complete pedagogical process of active methods of the organization of educational cognitive activity of pupils. The conceptual terms framework, operating which allows to solve problems of the conducted research is concretized. A complex of functions and didactic role performed by high-tech means of education have been identified, which makes it possible to determine the functional direction of the applied technical solutions taking into account their importance for the development of the personality of students in the conditions of the development of the knowledge economy and the era of digitalization. Technological and didactic aspects of integrating the innovative approach into the educational space of the Belarus have been identified. Sources of a research are the publications devoted to topical issues of development of STEM-education abroad and in the former Soviet Union including in Republic of Belarus.